Implementasi Thaharah Dalam Mengelola Hidup Bersih Dan Berbudaya - Eti Robiatul Adawiah; Ima Muslimatul Amanah; Yurna Yurna (LPPM Politeknik Pratama, 2023)
The purpose of writing is to provide a deep understanding of the concept of thaharah and the importance of its implementation in everyday life, explain the health benefits obtained through implementing thaharah, encourage behavior change and individual awareness in carrying out thaharah, provide education to the public about the concept of thaharah and implementation. The method used in this research is a qualitative method with a descriptive approach, the way to obtain data is in the form of literature studies, this research is carried out by reading and studying literature sources in the form of books and scientific journals regarding the implementation of thaharah in managing a clean and cultured life. This writing provides a deeper understanding of the factors that influence the application of thahrah in everyday life and how it can affect the overall quality of life. By involving individuals, families, communities and the government, the implementation of thaharah in managing a clean and cultured life brings real benefits and forms a healthy, clean and cultured society.